2013
DOI: 10.5598/imafungus.2013.04.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Oospores of Pustula helianthicola in sunflower seeds and their role in the epidemiology of white blister rust

Abstract: White blister rust (WBR) of sunflower caused by Pustula helianthicola is an important and often underestimated disease in many countries of the world. The epidemiology of the pathogen is not yet fully understood; particularly the role of oospores in primary infection and long distance dispersal. We analysed WBR severity in sunflower under natural conditions and found disease incidence of 97–99 % in fields where infected sunflower had first been observed ca. 8 yr ago. Besides the typical blisters of mitotic spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Recent examples such as for potato late blight, P. infestans, have shown that even with herbarized historic specimens from the 19th-century epidemics in Europe could be ascribed to a single introduction of a genetically distinctive strain (HERB-1) from North America (Yoshida et al, 2014). In another case, molecular and chemical analyses of the fatty acids of Pustula helianthicola sporangia taken from desiccated specimens showed near identity between samples from sunflower of Australia, South Africa and Germany indicating that the occurrence in Germany does not stem from white rusts on local Asteracean wild plants, but most likely from an unintended introduction with seeds from the southern hemisphere in which the pathogen is able to survive (Lava et al, 2013). However, studies based on specimens, especially historic ones, are prone to contamination with spores from other pathogens that are probably more readily amplifiable with a given primer set.…”
Section: Challenges For Population Studies With Biotrophic Oomycetesmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent examples such as for potato late blight, P. infestans, have shown that even with herbarized historic specimens from the 19th-century epidemics in Europe could be ascribed to a single introduction of a genetically distinctive strain (HERB-1) from North America (Yoshida et al, 2014). In another case, molecular and chemical analyses of the fatty acids of Pustula helianthicola sporangia taken from desiccated specimens showed near identity between samples from sunflower of Australia, South Africa and Germany indicating that the occurrence in Germany does not stem from white rusts on local Asteracean wild plants, but most likely from an unintended introduction with seeds from the southern hemisphere in which the pathogen is able to survive (Lava et al, 2013). However, studies based on specimens, especially historic ones, are prone to contamination with spores from other pathogens that are probably more readily amplifiable with a given primer set.…”
Section: Challenges For Population Studies With Biotrophic Oomycetesmentioning
confidence: 97%
“…Similar to the downy mildews, white blister rust species sexually form thick-walled oospores, which outlast unfavorable conditions. In sunflower white blister rust, Pustula helianthicola, oospores are formed homothallically and can also be found in achenes of the host, so they are easily distributed by seeds (Lava and Spring, 2012;Lava et al, 2013). Unlike in downy mildews, oospores are also used for discriminating species in white blister rusts (Choi et al 2007b(Choi et al , 2008Thines et al 2009a;Ploch et al 2010;Rost and Thines, 2012;Mirzaee et al 2013).…”
Section: A Specific Biological Featuresmentioning
confidence: 99%
“…Alternatively, a systematic study of the pathogen and its host preferences could help to find a long term sustainable solution without hazardous effects on the environment. Hence our previous studies had focused on central aspects in the life cycle of P. helianthicola such as the formation and infectivity of the oospores (Lava and Spring, 2012), or the role of seed contamination for overwintering and long distance propagation (Lava et al, 2013). However, the pathogen's host range and the susceptibility of sunflower crop lines are still understudied.…”
Section: Introductionmentioning
confidence: 99%